Origen, variabifity and damestication cl Hevea; a review - Gonçalves, Paulo de Souza; Cardoso, Mário; Ortolani, Altino Aldo (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this review is to point out the rubber tree (Hevea brasiliensis Muell. Arq.) domestication including the following steps: 1) Transference of the seeds by Wickham from Amazon to Kew, England, free from Soth American leaf blight (SALB) caused by Microcyclus ulei. 2)Development of a better tapping method by Ridley. 3) Vegetative propagation by bud grafting. 4) Yield increases and resistence to SALB from genetic improvements and 5) Use of chemical yield stimulants on the tapping panel. In addition the botany characters, area of occurrence and phenotypic variability of the species are pointed out in the center of genetic diversity near Negro river and tributaries from its confluence with the Amazon river into Colombia where seven species abound.